PENGEMBANGAN MEDIA PEMBELAJARAN AL-QURAN HADITS BERBASIS E-MODUL MELALUI SASTRA PUISI PADA MATERI BACAAN GHARIB - Moh. Maqbul; Abdulloh Hamid; Mohammad Solehuddin; Winarto Eka Wahyudi (POTENSIA: Jurnal Kependidikan Islam, 2021)
Understanding tajwid material, especially aboutreading gharib, must be presented in an attractive manner so that students can absorb the material well. So that the application in practice is also easier and not always the same. Therefore, this study aims to provide options related to variations in delivering learning material. By using themethod Research and Development (R&D) which produces a product in the form of an E-Module, this research was passed using several stages which are commonly abbreviated as themodel ADDIE (analysis, design, development, implementation and evaluation) and the results of this study show that on average Correspondents and validators from several experts (material, language, and media experts) stated that this E-Module-based media was feasible to use.